A chemically strengthened glass containing Y2O3 and its application

By introducing Y2O3 into the glass and chemically strengthening, the compression and tension stress layers are formed, the problem of insufficient scratch resistance of existing glass is solved, and the stability of scratch resistance and optical performance is significantly improved. It is suitable for smart devices and Extreme environment.

CN117486502BActive Publication Date: 2025-01-14CHONGQING AUREAVIA HI TECH GLASS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210887801.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-01-14
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

Existing glass products have shortcomings in scratch resistance and are difficult to meet market demand. Especially in use scenarios in smart devices and extreme environments, it is easy to cause optical performance and impact strength to decrease due to scratches.

Method used

Chemically strengthened glass containing Y2O3 is used to form a compressive stress layer and a tensile stress layer through chemical reinforcement process to improve the scratch resistance of the glass, meet specific stress characteristics and Young's modulus requirements, and prevent the expansion of cracks and scratches.

Benefits of technology

It significantly improves the scratch resistance of glass, reduces the scratch area and impact on optical performance, extends the crack propagation distance, and meets the market's demand for high-performance glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117486502B_ABST
    Figure CN117486502B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of glass technology, and specifically relates to a chemically strengthened glass containing Y2O3 and its application, wherein the chemically strengthened glass comprises a compressive stress layer and a tensile stress layer, and the chemically strengthened glass satisfies: surface CS ≥ 900MPa; (surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00, wherein CT_LD is the tensile stress line density, in units of MPa / mm; Young's modulus>85GPa. The chemically strengthened glass of the present invention has a specific stress structure, excellent chemical stress characteristics and high intrinsic strength, and excellent scratch resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass, and in particular relates to a chemically strengthened glass containing Y2O3 and application thereof. Background Art

[0002] With the popularization of electronic devices with touch display devices such as smart phones, tablets, electronic watches, and smart wearables, the era of human intelligent mobility has begun. Under this trend, the requirements for display screen performance are also constantly increasing, especially the requirements for the wear and scratch resistance of touch screens are also increasing.

[0003] Smartphone screens or car displays are prone to scratches due to abrasion or scratches during long-term use. If there are too many scratches or the scratch area is too large, it will cause visual discomfort and affect the visual effect. In addition, since scratches will scatter incident light, if there are too many scratches or the scratch area is too large, the impact on transparency and optical properties will be relatively large, such as reducing transmittance, refractive index, etc., and especially increasing the haze of the glass. For example, if the glass of the rear camera lens of a mobile phone has too many scratches or the scratch area is too large during long-term use, it will cause the mirror haze to be large, reducing the photographic imaging ability. In addition, scratches may also serve as the starting point for cracks in the touch screen glass. Under the influence of impact, collision, etc., unstable expansion will cause the glass's impact resistance to decrease, increase the possibility of failure, and lead to high subsequent repair / replacement costs.

[0004] The cover glass materials on current smartphones are usually developed with the focus on improving drop resistance. However, the scratch resistance that customers pay more attention to during use is often overlooked. As a result, the scratch resistance of current cover glass products is difficult to meet customer / market needs.

[0005] Smart wearable samples (such as watches, bracelets, etc.), display devices in extreme environments, and automotive intelligent control systems are all in fixed positions and do not have very high requirements for drop performance. However, due to frequent contact with hard objects and pressure, they require higher scratch resistance and wear resistance to maintain their good optical properties.

[0006] Therefore, in order to meet market demand, developing a glass product with excellent scratch resistance is a technical problem that urgently needs to be solved in this field. Summary of the invention

[0007] The purpose of the present invention is to overcome the defect that the scratch resistance of glass in the prior art needs to be further improved, and to provide a chemically strengthened glass containing Y2O3 and its application, wherein the chemically strengthened glass has excellent chemical stress characteristics and high intrinsic strength, and has excellent scratch resistance.

[0008] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a chemically strengthened glass containing Y2O3, wherein the chemically strengthened glass has a compressive stress layer formed by chemical strengthening on the surface, and has a tensile stress layer inside that can achieve force balance with the compressive stress layer, that is, the chemically strengthened glass comprises a compressive stress layer and a tensile stress layer, and the chemically strengthened glass satisfies:

[0009] Surface CS ≥ 900MPa;

[0010] (Surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00, where CT_LD is the tensile stress linear density, in MPa / mm;

[0011] Young's modulus>85GPa.

[0012] The chemically strengthened glass of the present invention, when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester, and a scratch with a length of 4.6 mm is formed under a load of 50 g, the area of ​​the scratch is less than 0.6 mm 2 .

[0013] The chemically strengthened glass of the present invention, when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester under a load of 200g to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6mm, the area of ​​the scratch is less than 1.5mm 2 .

[0014] The chemically strengthened glass of the present invention, when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester, and a load of no more than 200 g is used to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6 mm, the scratch does not cause edge chipping or the area of ​​the scratch with edge chipping does not exceed 5% of the total area of ​​the scratch.

[0015] According to some preferred embodiments of the present invention, the surface CS of the chemically strengthened glass is ≥1000 MPa, and more preferably the surface CS is 1000 MPa-1600 MPa.

[0016] According to some preferred embodiments of the present invention, the chemically strengthened glass satisfies: 2.00≥(surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00.

[0017] According to some preferred embodiments of the present invention, CT_LD of the chemically strengthened glass is ≥40000 MPa / mm, more preferably 40000 MPa / mm-66000 MPa / mm.

[0018] According to some preferred embodiments of the present invention, the Young's modulus of the chemically strengthened glass is ≥90 GPa, more preferably 90 GPa-110 GPa.

[0019] According to some preferred embodiments of the present invention, the chemically strengthened glass further satisfies: 0<DOL_1≤0.014t, wherein t is the thickness of the chemically strengthened glass, and DOL_1 is the depth of the compressive stress layer formed on any surface of the chemically strengthened glass by sodium-potassium exchange.

[0020] According to some preferred embodiments of the present invention, the chemically strengthened glass further satisfies: 0.14t≤DOL_0≤0.25t, wherein t is the thickness of the chemically strengthened glass, and DOL_0 is the depth of the compressive stress layer, in μm.

[0021] According to some preferred embodiments of the present invention, the Vickers hardness of the chemically strengthened glass is ≥650 kgf / mm 2 , more preferably 670kgf / mm 2 -750kgf / mm 2 .

[0022] According to some preferred embodiments of the present invention, the bifurcation threshold of the chemically strengthened glass is 40000 MPa / mm-60000 MPa / mm.

[0023] Preferably, CT_LD≤1.10×bifurcation threshold.

[0024] According to some preferred embodiments of the present invention, the composition of the chemically strengthened glass tensile stress layer includes, by molar percentage of oxides: a SiO2 content of 50.0%-80.0%, an Al2O3 content of 3.0%-20.0%, a Y2O3 content of 0.5%-10.0%, a La2O3 content of 0-10.0%, a MgO content of 0-15.0%, a Na2O content of 1.0%-10.0%, and a Li2O content of 1.0%-20.0%.

[0025] According to some preferred embodiments of the present invention, the composition of the chemically strengthened glass tensile stress layer includes, by molar percentage of oxides: a SiO2 content of 60.0%-70.0%, an Al2O3 content of 8.0%-15.0%, a Y2O3 content of 1.5%-6.0%, a La2O3 content of 0%-2.0%, a MgO content of 1.0%-7.5%, a Na2O content of 3.0%-6.0%, a Li2O content of 8.0%-12.0%, a ZrO2 content of 0-10%, a P2O5 content of 0-8%, and a SrO content of 0-10%.

[0026] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies:

[0027] The content is expressed as a molar percentage of the oxide, and the value of G is calculated based on the following formula, G≥1250,

[0028] G=SiO2×7.5+Al2O3×24+B2O3×2-P2O5×6+MgO×31.5+SrO×20+Y2O3×66+La2O3×57+Na2O×10.8+Li2O×25+K2O×7+ZnO×6.1+ZrO2×27.

[0029] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies the following relation: Na2O×(3Y2O3+Al2O3)>80, expressed in terms of the content expressed in molar percentage of oxides.

[0030] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies, in terms of content expressed in molar percentage of oxides: Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1.

[0031] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies:

[0032] The content is expressed as a molar percentage of the oxide, and the value of M is calculated based on the following formula, M≥12,

[0033] M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

[0034] In a second aspect, a substrate glass for preparing the chemically strengthened glass as described in the first aspect, wherein the composition of the substrate glass comprises, in terms of molar percentage of oxides: 50.0%-80.0% SiO2, 3.0%-20.0% Al2O3, 0.5%-10.0% Y2O3, 0-10.0% La2O3, 0-15.0% MgO, 1.0%-10.0% Na2O, and 1.0%-20.0% Li2O;

[0035] And the composition of the substrate glass satisfies the following conditions in terms of the content expressed as a molar percentage of oxides:

[0036] The value of G is calculated based on the following formula, G≥1250,

[0037] G=SiO2×7.5+Al2O3×24+B2O3×2-P2O5×6+MgO×31.5+SrO×20+Y2O3×66+La2O3×57+Na2O×10.8+Li2O×25+K2O×7+ZnO×6.1+ZrO2×27;

[0038] Na2O×(3Y2O3+Al2O3)>80.

[0039] Preferably, the composition of the substrate glass includes, in terms of molar percentage of oxides: SiO2 content of 60.0%-70.0%, Al2O3 content of 8.0%-15.0%, Y2O3 content of 1.5%-6.0%, La2O3 content of 0%-2.0%, MgO content of 1.0%-7.5%, Na2O content of 3.0%-6.0%, and Li2O content of 8.0%-12.0%.

[0040] Preferably, the composition of the substrate glass further comprises, in terms of molar percentage of oxides: a ZrO2 content of 0-10%, a P2O5 content of 0-8%, and a SrO content of 0-10%.

[0041] Preferably, the composition of the substrate glass further satisfies the following conditions, measured in terms of the content expressed as a molar percentage of oxides:

[0042] Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1; and / or

[0043] The value of M is calculated based on the following formula, M≥12,

[0044] M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

[0045] Preferably, the Young's modulus of the substrate glass is greater than 85 GPa, more preferably 90 GPa-110 GPa.

[0046] Preferably, the Vickers hardness of the substrate glass is ≥620kgf / mm 2 , more preferably 630kgf / mm 2 -750kgf / mm 2 .

[0047] Preferably, the bifurcation threshold of the substrate glass is 40000 MPa / mm-60000 MPa / mm.

[0048] In a third aspect, the present invention provides a glass device, wherein the glass device is made of the chemically strengthened glass described in the first aspect or the substrate glass described in the second aspect.

[0049] In a fourth aspect, the present invention provides an electronic device comprising a cover, wherein the cover comprises the chemically strengthened glass described in the first aspect.

[0050] The electronic device described in the present invention includes but is not limited to at least one of a mobile phone, a display, a tablet computer, an electronic watch, a smart wearable (such as a smart bracelet, a smart watch, smart glasses, etc.), a car-mounted device, an aircraft-mounted device, and a television.

[0051] The inventors of the present invention have found through continuous research that the scratch resistance of glass is closely related to the glass structure and the stress characteristics of glass strengthening. By making chemically strengthened glass have a high Young's modulus and meet specific stress characteristic requirements, the scratch resistance of glass can be significantly improved.

[0052] The present invention provides a chemically strengthened glass with a suitable high surface CS, (surface CS / 1000)×0.7+(CT_LD / 40000)×0.3 and Young's modulus at suitable levels, which has a specific stress structure, thereby significantly improving its scratch resistance, and can solve the shortcomings of glass being worn or scratched due to long-term use and affecting optical performance, and meet the increasingly high performance requirements of the market. Among them, since the generation and expansion of cracks and scratches will be subject to two resistances, the compressive stress layer and the network structure of the glass itself, the suitable high surface high stress (i.e., high surface CS) set by the present invention can prevent the generation of cracks and scratches, weaken their energy to expand inward, and at the same time, meet the stress characteristic requirements of the above formula and the suitable Young's modulus, so that the deep low-pressure stress area has a specific network structure and stress structure, which can extend the distance from the crack to the tensile stress area, and give full play to the strength of the glass network structure, both of which make it more difficult for cracks and scratches to expand and grow, thereby significantly improving its scratch resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0054] Figure 1The pictures are pictures of the scratches on the chemically strengthened glass of Example 1 under different weight conditions in the scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0055] Figure 2 The pictures are pictures of the scratches on the chemically strengthened glass of Example 2 under different weight conditions in the scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0056] Figure 3 The pictures are pictures of the scratches on the chemically strengthened glass of Example 3 under different weight conditions in the scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0057] Figure 4 The pictures are pictures of scratches on the chemically strengthened glass of Example 4 under different weight conditions in a scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0058] Figure 5 The pictures are pictures of the scratches on the chemically strengthened glass of Example 5 under different weight conditions in the scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0059] Figure 6 The pictures are pictures of the scratches on the chemically strengthened glass of Example 6 under different weight conditions in the scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0060] Figure 7The pictures are pictures of the scratches on the chemically strengthened glass of Example 7 under different weight conditions in the scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of the scratches under weight conditions of 0g, 50g, 100g, 150g, 200g, and 250g, respectively, after being magnified 43.9 times.

[0061] Figure 8 The figures are pictures of scratches on the chemically strengthened glass of Example 1 under different weight conditions in a scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of scratches under weight conditions of 0 g, 50 g, 100 g, 150 g, 200 g, and 250 g, respectively, after being magnified 43.9 times.

[0062] Fig. 9 The figures are pictures of scratches on the chemically strengthened glass of Example 2 under different weight conditions in a scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of scratches under weights of 0 g, 50 g, 100 g, 150 g, 200 g, and 250 g, respectively, after being magnified 43.9 times.

[0063] Fig.10 The figures are pictures of scratches on the chemically strengthened glass of Example 3 under different weight conditions in a scratch test using an automatic pencil hardness tester, wherein (a), (b), (c), (d), (e), and (f) are pictures of scratches under weight conditions of 0 g, 50 g, 100 g, 150 g, 200 g, and 250 g, respectively, after being magnified 43.9 times.

[0064] Fig.11 It is a structural schematic diagram of the stress relief device. DETAILED DESCRIPTION

[0065] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0066] Glossary and corresponding test methods:

[0067] Chemically strengthened glass: is strengthened glass that has been treated by high-temperature ion exchange process. In the high-temperature salt bath, alkali metal ions with large ion radius replace alkali metal ions with small ion radius in the glass, thereby generating exchange ion volume difference, generating high to low compressive stress in the surface layer of the substrate glass, hindering and delaying the expansion of microcracks in the glass, and achieving the purpose of improving the mechanical strength of the glass.

[0068] Base glass: glass matrix material that has not been strengthened.

[0069] Surface CS: surface compressive stress (also called surface compression stress). After the substrate glass is chemically strengthened, the alkali metal ions with smaller surface radius are replaced by alkali metal ions with larger radius. Due to the crowding effect of the alkali metal ions with larger radius, compressive stress is generated on the glass surface, which is called surface compressive stress.

[0070] DOL_0: Depth of compressive stress layer (also called compressive stress layer depth), refers to the distance from any surface of chemically strengthened glass to the position close to the surface where the compressive stress is zero. It is the depth of the compressive stress layer formed by lithium-sodium exchange (sodium ions in the salt bath / molten salt are exchanged with lithium ions in the glass) on any surface of chemically strengthened glass. Since the volume difference between lithium and sodium ions is small, the compressive stress layer formed by lithium-sodium exchange is deeper.

[0071] DOL_1: The depth of the compressive stress layer formed on any surface of chemically strengthened glass by sodium-potassium exchange (exchange of potassium ions in the salt bath / molten salt with sodium ions in the glass). Due to the large volume difference between sodium and potassium ions, the compressive stress layer formed by sodium-potassium exchange is shallow.

[0072] Stress parameter testing:

[0073] Surface CS, potassium-sodium stress exchange depth DOL_1 test conditions: Use Japan Orihara stress meter FSM-6000 for testing, the light source wavelength is 596nm. Before starting the test, fill in the thickness, refractive index, and photoelastic coefficient of the sample to be tested into the parameter table, and then test to obtain the stress parameter value of the sample to be tested.

[0074] Test conditions for DOL_0 and CT_LD: Use the stress meter SLP-2000 from Japan Orihara for testing, with a light source wavelength of 518nm. Before starting the test, fill in the thickness, refractive index, and photoelastic coefficient of the sample to be tested into the parameter table, adjust the exposure time to 5000usec, and then test to obtain the stress parameter values ​​of the sample to be tested.

[0075] Glasses of different compositions have different refractive indices and photoelastic coefficients. In the present invention, the refractive index is tested by an Abbe refractometer, and the photoelastic coefficient is tested by a UNIPT ABR-10A dual-frequency laser stress meter.

[0076] When using a stress meter to test the stress parameters of chemically strengthened glass products, you need to first drop a special refractive liquid on the stress meter, then wipe the chemically strengthened glass products clean, place them on the test path, and set up the instrument according to the above test conditions, and then test to obtain the stress parameter values ​​of the chemically strengthened glass. Among them, the refractive index of the refractive liquid used by SLP-2000 is 1.51, and the refractive index of the refractive liquid used by FSM-6000 is 1.72.

[0077] CT_LD: tensile stress line density. The substrate glass is placed in a salt bath for ion exchange to form a strengthening layer (compressive stress layer). During the ion exchange process, a tensile stress layer is formed inside the glass. The tensile stress layer has an upper boundary that is spaced a certain distance from the upper surface of the chemically strengthened glass and a lower boundary that is spaced a certain distance from the lower surface of the chemically strengthened glass. The tensile stress curve is a curve drawn with the tensile stress magnitude at a point on a line segment in the tensile stress layer that is perpendicular to the upper boundary and the lower boundary and whose upper and lower endpoints fall on the upper boundary and the lower boundary respectively as the Y axis and the distance from the corresponding point to the upper boundary as the X axis. The ratio of the definite integral of the tensile stress curve to the thickness of the chemically strengthened glass is recorded as the tensile stress line density. That is, the ratio of the sum of the tensile stresses of the strengthened glass measured by the SLP_2000 stress meter to the glass thickness.

[0078] Edge chipping phenomenon: refers to the unevenness, curling, and rough edges that appear at the scratched part of the glass.

[0079] Young's modulus E test: The Young's modulus is measured by the sonic method, which is used to characterize the ability of glass to resist elastic deformation due to external forces. The method for testing the Young's modulus in the present invention is the sonic method, and the instrument model is MK7 produced by Kegonas Instrument Trading Co., Ltd.

[0080] Bifurcation threshold: When a chemically strengthened glass prepared from a certain formula base glass undergoes an immediate fracture test and a glass crack bifurcates, the minimum tensile stress linear density value of the chemically strengthened glass is the bifurcation threshold of the chemically strengthened glass prepared from the formula base glass.

[0081] The immediate fracture test: the center point of the chemically strengthened glass sample is used as the breaking point, and a "stress release device" is used to generate cracks at the breaking point, so that the cracks extend under the action of the internal tensile stress, rather than generating starbursts due to excessive impact force. When the crack of the chemically strengthened glass bifurcates, the minimum tensile stress line density value of the chemically strengthened glass sample is the bifurcation threshold. A certain number of substrate glass products are strengthened under the same salt bath conditions for different ion exchange times to obtain glass samples with different tensile stress line densities. According to the tensile stress line density values ​​from low to high, an immediate fracture test is performed on the multiple glass samples obtained by strengthening. After the immediate fracture test, check whether the crack of the glass sample bifurcates, find the glass samples with bifurcated cracks, and determine the minimum tensile stress line density (CT_LD) value of these glass samples, which is the bifurcation threshold of the chemically strengthened glass prepared by the substrate glass.

[0082] The stress relief device Fig.11 , where 1 represents the height adjustment rail, 2 represents the start adjustment rail, 3 represents the indenter, and 4 represents the chemically strengthened glass sample; the device adopts pneumatic impact, and the probe adopts a Vickers diamond indenter and is fixed with a rail to ensure that the indenter impacts the glass surface vertically, and is equipped with a pressure sensor, which controls the impact force in combination with air pressure regulation, so that the destruction point only induces delayed fracture or only extends two cracks instead of producing a starburst, thereby minimizing the influence of external force on the destruction state.

[0083] The specific test method of the bifurcation threshold in the present invention is: first test the maximum value of the tensile stress linear density CT_LD that can be obtained by a substrate glass with a thickness of 0.7 mm corresponding to a certain glass formula in a 100wt% sodium nitrate salt bath at 450°C. max Then, the strengthened glass samples with different CT_LD were strengthened under the salt bath conditions, ranging from 30000MPa / mm to CT_LD max, increasing by about 1000MPa / mm, 1500MPa / mm or 2000MPa / mm, that is, the present invention uses the above-mentioned salt bath conditions, i.e., 100wt% sodium nitrate salt bath at 450°C, to strengthen the substrate glass with a thickness of 0.7mm corresponding to the glass formula to be tested to obtain chemically strengthened glass samples with CT_LD of about 30000MPa / mm, about 31000MPa / mm, about 32000MPa / mm, about 33000MPa / mm, about 34000MPa / mm, about 36000MPa / mm..., and then these chemically strengthened glass samples are subjected to fracture experiments in order of CT_LD values ​​from low to high. The center point of the chemically strengthened glass sample is used as the failure point, and the above-mentioned "stress release device" is used to cause cracks to form at the failure point. The chemically strengthened glass samples with bifurcated cracks were screened out, and the minimum CT_LD value of the screened chemically strengthened glass samples was used as the bifurcation threshold of the chemically strengthened glass prepared from the base glass of the formula. The CT_LD value was measured using an SLP-2000 stress meter.

[0084] The bifurcation threshold is a reference indicator for the glass to be able to safely accommodate stress.

[0085] Note that when the CT_LD of the strengthened glass sample has reached CT_LD max , and an immediate fracture test is performed on it. It is found that the glass crack still does not bifurcate. It is judged that the bifurcation threshold of this formula glass is greater than the CT_LD that can be obtained under the salt bath conditions. max .

[0086] CT_LD max Test: The maximum tensile stress linear density (CT_LD) value that can be obtained by ion exchange chemical strengthening of the substrate glass under specific salt bath conditions is the maximum tensile stress linear density CT_LD that the substrate glass can obtain under the salt bath conditions. max This data can characterize the chemical strengthening / ion exchangeability of the substrate glass.

[0087] During the chemical strengthening process, as the strengthening time increases, the tensile stress linear density (CT_LD) value of the substrate glass will first increase and then decrease. By continuously monitoring the changes in the tensile stress linear density inside the glass during the strengthening process, the maximum tensile stress linear density CT_LD that can be obtained under specific salt bath conditions can be determined. max .

[0088] In the present invention, CT_LD max The test method:

[0089] In the present invention, a 100wt% sodium nitrate bath at 450°C is used as the test CT_LDmax Under salt bath conditions, SLP_2000 stress meter was used as the testing instrument for testing tensile stress linear density CT_LD.

[0090] The specific method is: place the substrate glass sample to be tested in a 100wt% sodium nitrate salt bath at 450°C for chemical strengthening. During the strengthening period, take out the glass sample every 0.5h to test its internal CT_LD value. After each glass sample is taken out for testing, immediately put the glass sample into the salt bath to continue strengthening. When the next test time point is reached, take out the glass sample for testing again, repeat the above test process, and record the CT_LD value of the test. When it is found that the measured CT_LD value begins to decrease after increasing to a certain value m, the value m is determined to be the maximum value of the tensile stress linear density CT_LD that can be obtained by strengthening the substrate glass sample under the salt bath conditions, that is, a 100wt% sodium nitrate salt bath at 450°C. max .

[0091] The test method of Vickers hardness is as follows: a digital low-load Vickers hardness tester with a microscopic observation device is used for testing, a diamond regular pyramid indenter with a vertex angle of 136° is used to vertically press into the surface of the tested sample under a specified load F (the sample load of the present invention is 300 gf), the load is unloaded after a specified time (the sample holding time of the present invention is 10 s), the indentation surface area is calculated according to the diagonal length of the indentation, and the average pressure on the indentation surface area is converted into Vickers hardness; the present invention performs 6 micro-Vickers hardness tests on a single sample, and takes the average value as the micro-Vickers hardness test result of the sample.

[0092] The test method for fracture toughness is:

[0093] On a digital display small load Vickers hardness tester, a diamond regular pyramid indenter with a vertex angle of 136° is pressed into the sample surface with a certain load (the sample load of the present invention is 300gf), and the load is unloaded after a specified time (the sample holding time of the present invention is 10s). The extension length of the diagonal crack of the indentation is measured with a microscope. In order to ensure the accuracy of the data, each sample is tested 6 times, and the average length of the crack is taken as the test value. The fracture toughness is calculated based on the load P (in kg) and the extension length D of the indentation crack (in mm) to characterize the material's ability to prevent crack extension. The calculation formula for fracture toughness is:

[0094]

[0095] In a first aspect, the present invention provides a chemically strengthened glass containing Y2O3, wherein the chemically strengthened glass has a compressive stress layer formed by chemical strengthening on the surface, and has a tensile stress layer inside that can achieve force balance with the compressive stress layer, and the chemically strengthened glass satisfies:

[0096] Surface CS ≥ 900MPa;

[0097] (Surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00, where CT_LD is the tensile stress linear density, in MPa / mm;

[0098] Young's modulus>85GPa.

[0099] The inventors of the present invention have found that the effects of surface CS and CT_LD on the scratch resistance are different, and further found that (surface CS / 1000)×0.7+(CT_LD / 40000)×0.3 can characterize the effect of stress degree on the scratch resistance, and the higher the calculated value, the higher the scratch resistance; and when the value is greater than 1, the chemically strengthened glass has excellent scratch resistance and can meet the needs of customers / market.

[0100] Preferably, the chemically strengthened glass satisfies: 2.00≥(surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00. Under this preferred embodiment, the high-stress surface CS that satisfies this formula can effectively prevent the generation of cracks and scratches, weaken the energy of microcracks extending inward, and the deep low-compression stress area can effectively extend the distance from the crack to the tensile stress area, and give full play to the strength of the glass network structure. The combination of the two makes it more difficult for cracks and scratches to expand and grow, thereby ensuring that the stress structure of the chemically strengthened glass is more suitable for improving its scratch resistance at a better level.

[0101] The value of (surface CS / 1000)×0.7+(CT_LD / 40000)×0.3 can be, for example, any value of 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, etc. and any value between adjacent values; more preferably, it is greater than 1.15.

[0102] In the preferred embodiment of the present invention, the surface CS of the chemically strengthened glass is ≥ 1000 MPa, and more preferably the surface CS is 1000 MPa-1600 MPa. In the preferred embodiment of the present invention, the greater the surface compressive stress value, the higher the mechanical strength of the chemically strengthened glass, and the better the scratch resistance.

[0103] The surface CS of the chemically strengthened glass can be, for example, any value among 1000, 1100, 1150, 1200, 1210, 1220, 1230, 1240, 1250, 1260, 1280, 1300, 1400, 1500, 1600 MPa, and any value between adjacent values; more preferably ≥1220 MPa.

[0104] In some preferred embodiments of the present invention, the CT_LD of the chemically strengthened glass is ≥ 40000 MPa / mm, more preferably 40000 MPa / mm-66000 MPa / mm. In this preferred embodiment, the tensile stress layer structure of the chemically strengthened glass is suitable, which can avoid the destructive force of scratches to the greatest extent, reduce the probability of edge collapse during scratching, thereby significantly reducing the scratch area, thereby improving the scratch resistance.

[0105] The tensile stress linear density CT_LD of the chemically strengthened glass may be, for example, any value of 40000, 41000, 42000, 43000, 44000, 44200, 44300, 44400, 44500, 44600, 44700, 44900, 45000, 47000, 49000, 50000, 60000, 62000, 64000, 66000 MPa / mm, and any value between adjacent values; more preferably ≥44200 MPa / mm.

[0106] In the present invention, the Young's modulus of the chemically strengthened glass is preferably ≥ 90 GPa, more preferably 90 GPa-110 GPa. Under this preferred embodiment, the chemically strengthened glass has a high Young's modulus, which is more conducive to synergizing with the appropriate range of surface CS and CT_LD to promote the formation of a stress structure with excellent scratch resistance. The Young's modulus of the chemically strengthened glass can be, for example, any value among 90, 91, 92, 93, 95, 97, 99, 100, 102, 105, 106, 108, 110 GPa, etc., and any value between adjacent values.

[0107] The chemically strengthened glass of the present invention, when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester, and a scratch with a length of 4.6 mm is formed under a load of 50 g, the area of ​​the scratch is less than 0.6 mm 2 The chemically strengthened glass of the present invention has a small scratch area and good anti-scratch performance.

[0108] In the present invention, the Mohs hardness pen is a pen-shaped testing tool in which a mineral in the Mohs hardness is embedded on a metal rod. The mineral corners of the pen tip are used to scratch the object to be tested, and the hardness of the object to be tested is judged based on whether scratches are left: if scratches are left, it means that the hardness of the object to be tested is lower than that of the hardness pen, and if scratches cannot be made, it means that the hardness of the object to be tested is higher than that of the hardness pen. The scratch resistance is characterized by the scratch area and the edge collapse of the scratches. Specifically, the test method for characterizing the scratch resistance by the Mohs hardness pen test is: using an automatic pencil hardness tester, fixing the Mohs hardness pen at a 45° angle, and moving the glass placement table at a rate of 64 mm / min under a predetermined load, and the predetermined load is a fixed weight. Mohs hardness pen is divided into ten hardness levels, and the Mohs hardness levels of ten minerals are: 10 diamond, 9 corundum, 8 topaz, 7 quartz, 6 feldspar, 5 apatite, 4 fluorite, 3 calcite, 2 gypsum, 1 talc; in order to better simulate the scene in life, the scratches of smart phones in application are mainly caused by fine dust and rough ground particles, cement ground, etc. in life. Among them, the most common and hardest substance is silica particles, and its hardness is between 7-8. Therefore, the present invention adopts a Mohs hardness pen with a hardness level of 8. The present invention uses a Mohs hardness pen with a hardness level of 8 to gradually increase the predetermined load level (0, 50, 100, 150, 200, 250g, which is the load of common mobile phones in life, and the weight of mobile phones is generally 150-200g) to scratch the surface of the glass sample until the sample shows unacceptable damage. The width, area and edge collapse of the scratches on the glass surface scratched by the Mohs hardness pen are observed to characterize the scratch resistance of the tempered glass.

[0109] The method for calculating the area of ​​the scratch of the present invention is: according to the resolution of the known scratch-containing image, according to the pixels of the irregular graphic part corresponding to the scratch, the area of ​​the irregular graphic scratch is calculated. Specifically, the area of ​​the scratch is obtained using professional image processing software (such as GIMP, GNU Image Manipulation Program, etc.), and the area is calculated as follows: pixels found in the histogram / square of the resolution = area of ​​the scratch. To ensure data accuracy, each image is measured three times to obtain the average value. Among them, the resolution refers to the number of pixels per unit length, and the unit length can be inches or centimeters.

[0110] The chemically strengthened glass of the present invention, when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester under a load of 200g to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6mm, the area of ​​the scratch is less than 1.5mm 2 The chemically strengthened glass of the present invention has a smaller scratch area under a higher load, and the scratch resistance can still be maintained at a good level.

[0111] The chemically strengthened glass of the present invention has a haze of no more than 0.15 when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45 degrees and a load of 50 g is used to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6 mm. The chemically strengthened glass of the present invention has a small influence on its optical properties after a certain scratch, and does not affect the application requirements.

[0112] In the present invention, haze has the conventional meaning in this field. The test method of haze is: select sample glass (the thickness of the glass remains the same, all are 0.7mm. The surface roughness Ra of the glass after flat grinding is less than 0.04μm), each piece of glass has a scratch in the middle, and the scratched and cleaned glass is placed in the middle of the Konica Minolta CM-3600A optical tester (so that the scratch is in the middle of the measurement area), and the optical performance is tested in the transmittance mode to explore the effect of scratches on the optical performance. The test conditions are: in the transmittance mode, opacity / haze index mode, the measurement area is LAV (25.4mm), D65 light source, haze: Haze (D1003-97) (A), Haze (D1003-97) (C), and the spectral wavelength range is 360nm to 740nm. The haze value of unscratched glass is less than 0.1.

[0113] The chemically strengthened glass of the present invention has a haze of no more than 0.40 when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45 degrees and a load of 200 g to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6 mm. The chemically strengthened glass of the present invention has a small influence on its optical properties after a certain scratch, and does not affect the application requirements.

[0114] The chemically strengthened glass of the present invention, when a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester, and a load of no more than 200 g (≤200 g load) is used to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6 mm, the scratch does not cause edge chipping or the area of ​​the scratch with edge chipping does not exceed 5% of the total area of ​​the scratch.

[0115] The inventors of the present invention have found that the surface scratch resistance is closely related to the surface CS. In order to ensure a high surface CS, in some preferred embodiments of the present invention, the chemically strengthened glass is also required to meet the following requirements: 0<DOL_1≤0.014t, more preferably 0<DOL_1≤0.010t, wherein t is the thickness of the chemically strengthened glass (the thickness of the substrate glass is very small compared to the thickness of the chemically strengthened glass obtained by chemically strengthening the substrate glass, and can be ignored), and DOL_1 is the depth of the compressive stress layer formed by sodium-potassium exchange on any surface of the chemically strengthened glass. For example, when the thickness of the chemically strengthened glass is 0.7 mm, DOL_1≤9.8 μm, preferably ≤7 μm. Under this preferred embodiment, DOL_1 is more suitable and can form a compressive stress layer with a high surface CS, thereby improving the scratch resistance of the chemically strengthened glass.

[0116] The inventors of the present invention found that surface CS is generated by potassium-sodium exchange. The higher volume difference of potassium-sodium ion exchange enables the glass surface to obtain high surface compressive stress. As the exchange time increases, potassium ions continue to enter the interior to increase DOL_1, and under the effect of stress relaxation, the surface CS gradually decreases; this is manifested as an increase in DOL_1 while a decrease in surface CS. Therefore, controlling DOL_1 is beneficial to ensuring that the surface CS is at a higher level.

[0117] According to some preferred embodiments of the present invention, the chemically strengthened glass further satisfies: 0.14t≤DOL_0≤0.25t, more preferably 0.14t≤DOL_0≤0.19t, wherein t is the thickness of the chemically strengthened glass, and DOL_0 refers to the depth of the compressive stress layer, in μm. Under this preferred embodiment, DOL_0 is suitable, has excellent drop resistance, and can effectively reduce the edge collapse caused by scratches, reduce the width of the edge collapse, thereby reducing the scratch area and reducing the impact on haze.

[0118] Generally, the unit of t is mm. The thickness of the chemically strengthened glass described in the present application is not particularly limited. For example, the thickness of the electronic device used in the touch display device can be 0.4-1.5 mm, for example, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, or a range formed by any two of the above values ​​as endpoints.

[0119] Preferably, the chemically strengthened glass has a Vickers hardness of ≥650 kgf / mm 2 , more preferably 670kgf / mm 2 -750kgf / mm 2The Vickers hardness of the chemically strengthened glass may be, for example, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, or 750 kgf / mm 2 Any value in between and any value between adjacent values.

[0120] According to some preferred embodiments of the present invention, the bifurcation threshold of the chemically strengthened glass is 40000MPa / mm-60000MPa / mm. The bifurcation threshold of the chemically strengthened glass can be, for example, any value among 40000, 41000, 42000, 43000, 44000, 45000, 46000, 47000, 50000, 52000, 55000, 57000, 60000MPa / mm, etc., and any value between adjacent values.

[0121] Preferably, CT_LD≤1.10×bifurcation threshold. Under this preferred embodiment, the deep stress is appropriate and the internal tensile stress is appropriately controlled, which helps to effectively avoid the interaction between the internal tensile stress and the destructive force of scratches, thereby effectively reducing the probability of edge collapse during the scratching process, thereby significantly reducing the scratch area, and significantly improving the scratch resistance. In the application field such as mobile phone cover, after the substrate glass is chemically strengthened, the higher the CT_LD value, the stronger its drop resistance. However, as the CT_LD value increases, the difference between it and the glass bifurcation threshold will gradually increase. When the difference between the two exceeds a certain limit, the probability of glass breaking into large fragments will become smaller, and a large number of small fragments will be generated, resulting in touch failure and display failure. Moreover, there are too many small fragments, which are prone to splashing and causing personal injury. By controlling the CT_LD value to not exceed 1.10 times the bifurcation threshold, the present application can ensure that the obtained chemically strengthened glass can maintain larger fragments after breaking, and can continue to be used without immediate failure.

[0122] More preferably, 0.5×bifurcation threshold<CT_LD≤1.10×bifurcation threshold.

[0123] In some preferred embodiments of the present invention, the composition of the chemically strengthened glass tensile stress layer includes, in terms of molar percentage of oxides: SiO2 content of 50.0%-80.0%, Al2O3 content of 3.0%-20.0%, Y2O3 content of 0.5%-10.0%, La2O3 content of 0-10.0%, MgO content of 0-15.0%, Na2O content of 1.0%-10.0%, and Li2O content of 1.0%-20.0%. During chemical strengthening, ions with large radius in the salt bath are exchanged with ions with small radius in the glass, thereby forming a compressive stress layer on the surface of the glass and a tensile stress layer inside the glass. Compared with the substrate glass before strengthening, the occurrence of ion exchange will cause the composition of the compressive stress layer to change. Since the ion exchange depth is usually less than or equal to the thickness of the compressive stress layer, the composition of the tensile stress layer inside the glass will not change, that is, the composition of the tensile stress layer is the same as that of the substrate glass before strengthening.

[0124] More preferably, the composition of the chemically strengthened glass tensile stress layer includes, by molar percentage of oxides: a SiO2 content of 60.0%-70.0%, an Al2O3 content of 8.0%-15.0%, a Y2O3 content of 1.5%-6.0%, a La2O3 content of 0-2.0%, preferably 0.5%-2.0%, a MgO content of 1.0%-7.5%, preferably 4.0%-7.0%, a Na2O content of 3.0%-6.0%, and a Li2O content of 8.0%-12.0%; and optionally, a ZrO2 content of 0-10%, a P2O5 content of 0-8%, and a SrO content of 0-10%.

[0125] In the above-mentioned preferred specific composition of the tension layer of the present invention, the chemically strengthened glass can have the above-mentioned specific stress structure, which is more conducive to improving its scratch resistance.

[0126] The chemically strengthened glass tensile stress layer may or may not include other element oxides as long as they are beneficial to improving the scratch resistance; other element oxides may include at least one of the oxides of K, Zn, Zr, B, P, and Sr.

[0127] In some embodiments of the present invention, the chemically strengthened glass tensile stress layer further comprises: a ZnO content of 0-1%, calculated as a molar percentage of oxides.

[0128] In some embodiments of the present invention, the chemically strengthened glass tensile stress layer further comprises: a ZrO2 content of 0-2%, calculated as a molar percentage of oxides.

[0129] In some embodiments of the present invention, the chemically strengthened glass tensile stress layer further comprises, in terms of molar percentage of oxides, a B2O3 content of 0-0.5%, preferably excluding B2O3.

[0130] In some embodiments of the present invention, the chemically strengthened glass tensile stress layer further comprises, in terms of molar percentage of oxides, a P2O5 content of 0-1.0%, preferably 0-0.5%.

[0131] In some embodiments of the present invention, the chemically strengthened glass tensile stress layer further comprises: SrO content of 0-3%, calculated as a molar percentage of oxides.

[0132] According to some preferred embodiments of the present invention, the chemically strengthened glass does not contain K2O.

[0133] In the present invention, the functions of each component element are as follows:

[0134] Si 4+ It is a network former component of glass, which has the effect of maintaining glass stability and viscosity suitable for molten glass forming, and improving the chemical stability of glass. 4+ If the content of SiO2 is too high, the glass will be difficult to melt, so SiO2 is limited to the above-mentioned suitable range. In the present invention, the content of SiO2 is any value among 50.0, 55.0, 58.0, 60.0, 62.0, 64.0, 65.0, 67.0, 69.0, 70.0, 72.0, 75.0, 77.0, 79.0, 80.0 mol % and any value between adjacent values.

[0135] Al 3+ It is a network former component of glass. 3+ It can improve the chemical stability of glass and help to form a loose glass grid, making it easy for the glass to increase its strength through chemical strengthening ion exchange process. At the same time, the glass contains an appropriate amount of Al 3+ It also reduces the possibility of glass breaking when it is scratched or pressed by hard objects. 3+ The formed aluminum-oxygen tetrahedron can increase the ion exchange rate and the stress effect produced by unit ion exchange. 3+ Too much content will make it difficult to eliminate the internal defects such as bubbles, streaks and stones in the glass. Therefore, Al2O3 is limited to the above-mentioned suitable range. In the present invention, the content of Al2O3 is any value among 3.0, 5.0, 8.0, 10.0, 12.0, 13.0, 15.0, 17.0, 18.0, 19.0, 20.0 mol% and any value between adjacent values.

[0136] Mg2+ It is a network intermediate component of glass. Mg 2+ It has a strengthening effect on the glass network, and also has the effect of improving the glass melting property and lowering the glass softening temperature. 2+ Too much content will reduce the chemical strengthening performance of the glass, especially reduce the ion exchange rate. Therefore, MgO is limited to the above-mentioned suitable range. In the present invention, the content of MgO is any value among 0, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 7.5, 8.0, 10.0, 12.0, 13.0, 14.0, 15.0 mol% and any value between adjacent values.

[0137] Li + It is the main component of ion exchange, Li + The increase in content is beneficial to increase the exchange amount of sodium-lithium ions and to increase the deep compressive stress. Therefore, Li2O is limited to the above-mentioned suitable range. In the present invention, the content of Li2O is any value among 1.0, 3.0, 5.0, 8.0, 9.0, 10.0, 11.0, 12.0, 15.0, 18.0, 20.0 mol% and any value between adjacent values.

[0138] Na + It is the main component of ion exchange and the key exchange ion for forming high surface compressive stress. Therefore, Na2O is limited to the above-mentioned suitable range. In the present invention, the content of Na2O is any value among 1.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0 mol% and any value between adjacent values.

[0139] However, excessive amounts of alkali metal components such as sodium and lithium will destroy the silicon-oxygen bonds in the glass, destroy the network structure, and reduce the intrinsic strength. Therefore, generally, the total amount of alkali metal oxides does not exceed 17.0 mol%, that is, the total amount of Li2O+Na2O+K2O does not exceed 17.0 mol%.

[0140] La 3+ It is a network modification component of glass. 3+ It can reduce the high temperature viscosity of glass, facilitate glass melting and eliminate internal defects, significantly improve the Young's modulus and Vickers hardness of glass, and also improve the chemical strengthening performance of glass and the stress effect of unit ion exchange of chemically strengthened glass. 3+ 、Al 3+ They jointly promote ion exchange to produce better stress effect. Therefore, La2O3 is limited to the above suitable range.

[0141] Y 3+It has the function of making the glass structure compact and can increase the packing density inside the glass, which is manifested as increasing the density of the glass, thereby increasing the intrinsic strength of the glass. For ion exchange performance, it can increase the Na + , Li + The stress effect produced by the unit ion exchange of plasma in the chemical strengthening process, but it will reduce its exchange rate. Therefore, Y2O3 is limited to the above-mentioned suitable range. In the present invention, the content of Y2O3 is any value among 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 7.0, 8.0, 9.0, 10.0 mol% and any value between adjacent values.

[0142] Sr 2+ It has a larger ion radius, and when the content is low, it has the effect of reducing the melting temperature of the glass and can reduce the crystallization speed of the crystallized glass. Therefore, the content of SrO is preferably 0-10%, and more preferably 0%-3%.

[0143] B 3+ It is the network former component of glass. 3+ It can improve the melting process of glass batch materials and significantly reduce the high temperature viscosity of molten glass; however, B 3+ Too high a content of B will reduce the chemical strengthening properties of the glass. 3+ In glass, there are two coordination states: [BO3] and [BO4]. The [BO4] coordination structure is stronger than [BO3], but the BO bond length is too short, which seriously reduces the ion migration efficiency during the chemical strengthening process. Therefore, the content of B2O3 is 0-0.5%.

[0144] P 5+ It is a network forming component of glass. 5+ It has the effect of improving the melting property of glass and reducing the crystallization property of glass. 5+ It can also modify the glass network and increase the chemical strengthening effect of the glass. 5+ It is easy to volatilize in continuous production, and the volatiles fall into the glass liquid, resulting in uneven composition. 5+ Glass is prone to phase separation at low temperatures in electric melting and all-platinum continuous melting production lines, which is not conducive to glass production. In addition, the double-bond asymmetric phosphorus-oxygen tetrahedrons formed by excessive P2O5 will lead to a decrease in mechanical strength, especially surface hardness, making the glass very easy to scratch. Therefore, P2O5 is limited to the above-mentioned suitable range.

[0145] Zr 4+ It is an intermediate oxide of glass, which can improve the chemical stability of glass, increase the surface hardness of glass, and is an effective component for improving the toughness of glass. Excessive ZrO2 will lead to the crystallization trend of glass and reduce the resistance to devitrification.

[0146] Zn 2+ It is an intermediate oxide of glass, which can reduce the low-temperature viscosity of glass and improve its chemical and thermal stability. Excessive ZnO will cause phase separation of glass and reduce its resistance to devitrification.

[0147] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies:

[0148] The content is expressed as a molar percentage of the oxide, and the value of G is calculated based on the following formula, G≥1250,

[0149] G=SiO2×7.5+Al2O3×24+B2O3×2-P2O5×6+MgO×31.5+SrO×20+Y2O3×66+La2O3×57+Na2O×10.8+Li2O×25+K2O×7+ZnO×6.1+ZrO2×27.

[0150] More preferably, G is greater than 1250. In this preferred embodiment, the chemically strengthened glass has very high intrinsic strength, which is more conducive to improving the scratch resistance.

[0151] The G described in the present invention can be, for example, any value among 1280, 1300, 1320, 1350, 1360, 1370, 1380, 1400, 1430, 1450, 1470, 1500, 1550, and 1600, or any value between adjacent point values.

[0152] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies the following conditions: Na2O×(3Y2O3+Al2O3)>80, and can be, for example, any value among 81, 85, 90, 100, 110, 120, 126, 130, 135, 140, etc., or any value between adjacent point values, in terms of the content expressed as a molar percentage of oxides. The preferred embodiment of the present invention is more conducive to obtaining chemically strengthened glass with high surface CS, thereby being more conducive to improving the scratch resistance of chemically strengthened glass.

[0153] Further preferably, the composition of the chemically strengthened glass tensile stress layer, expressed in terms of the content expressed in molar percentage of oxides, satisfies: Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1. This preferred embodiment of the present invention can promote the network structure stability of the surface compressive stress layer in the chemically strengthened glass, and the content of Li2O is greater than the sum of the total contents of Na2O and K2O, which can give full play to the aggregation effect of lithium ions, thereby being more conducive to improving the Young's modulus of the chemically strengthened glass, and further contributing to improving the scratch resistance.

[0154] In some preferred embodiments, 1<Li2O / (Na2O+K2O)≤4.0.

[0155] Further preferably, the composition of the chemically strengthened glass tensile stress layer satisfies:

[0156] The content is expressed as a molar percentage of the oxide, and the value of M is calculated based on the following formula, M≥12,

[0157] M = Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O). In this preferred embodiment, the ion exchange can have high exchange efficiency and high exchange capacity, which helps to improve the compactness of the chemically strengthened glass, thereby helping to obtain chemically strengthened glass with high deep stress CT_LD, thereby improving the scratch resistance. Specifically, since Li2O is the main factor determining the amount of sodium-lithium ion exchange, and the exchange efficiency is related to the density of the glass, the inventors have found that Y2O3, La2O3, and Al2O3 can all be used to improve the density of the glass, but the degree of effect is different. Y2O3 has the greatest effect, La2O3 is second, and Al2O3 is the smallest. The free oxygen produced by alkali metals and alkaline earth metals will destroy the network and reduce the density. The ability of MgO, Li2O, K2O, and Na2O to provide free oxygen is also different. K2O and Na2O have the largest amount, while MgO and Li2O are smaller. Based on this, the inventors have further found that the above formula can express the degree of exchange efficiency combined with the exchange amount. The higher the M value, the higher the deep stress will be, which is more helpful to improve the scratch resistance.

[0158] The M described in the present invention can be, for example, any value of 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, etc., or any value between adjacent point values.

[0159] In some preferred embodiments, 12≤M≤35.

[0160] The chemically strengthened glass of the present invention can be applied to the field of cover plate protection of electronic devices, such as smart phones, smart wearables (such as smart bracelets, smart watches, smart glasses), etc., as well as display protection of pressure-resistant equipment in extreme environments, and is also applicable to the automotive field, such as protection of vehicle-mounted display equipment, etc.

[0161] In a second aspect, a substrate glass for preparing the chemically strengthened glass according to the first aspect, wherein the composition of the substrate glass comprises, in terms of molar percentage of oxides: 50.0%-80.0% SiO2, 3.0%-20.0% Al2O3, 0.5%-10.0% Y2O3, 0-10.0% La2O3, 0-15.0% MgO, 1.0%-10.0% Na2O, and 1.0%-20.0% Li2O;

[0162] And the composition of the substrate glass satisfies the following conditions in terms of the content expressed as a molar percentage of oxides:

[0163] The value of G is calculated based on the following formula, G≥1250,

[0164] G=SiO2×7.5+Al2O3×24+B2O3×2-P2O5×6+MgO×31.5+SrO×20+Y2O3×66+La2O3×57+Na2O×10.8+Li2O×25+K2O×7+ZnO×6.1+ZrO2×27;

[0165] Na2O×(3Y2O3+Al2O3)>80.

[0166] The present invention enables the substrate glass to have a specific composition so that it has a very high surface compressive stress after ion exchange, thereby having excellent surface anti-scratch performance.

[0167] Preferably, the composition of the substrate glass includes, in terms of molar percentage of oxides: SiO2 content of 60.0%-70.0%, Al2O3 content of 8.0%-15.0%, Y2O3 content of 1.5%-6.0%, La2O3 content of 0%-2.0%, MgO content of 1.0%-7.5%, Na2O content of 3.0%-6.0%, and Li2O content of 8.0%-12.0%.

[0168] Preferably, the composition of the substrate glass further comprises, in terms of molar percentage of oxides: a ZrO2 content of 0-10%, a P2O5 content of 0-8%, and a SrO content of 0-10%.

[0169] Preferably, the composition of the substrate glass further satisfies the following conditions, measured in terms of the content expressed as a molar percentage of oxides:

[0170] Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1; and / or

[0171] The value of M is calculated based on the following formula, M≥12,

[0172] M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

[0173] Preferably, the Young's modulus of the substrate glass is greater than 85 GPa, more preferably 90 GPa-110 GPa.

[0174] Preferably, the Vickers hardness of the substrate glass is ≥620kgf / mm 2 , more preferably 630kgf / mm 2 -750kgf / mm 2 .

[0175] Preferably, the bifurcation threshold of the substrate glass is 40000 MPa / mm-60000 MPa / mm.

[0176] The present invention has a wide range of options for the preparation method of the chemically strengthened glass mentioned above. As long as the required conditions such as the above-mentioned stress structure characteristics are met, the chemically strengthened glass can be guaranteed to have excellent scratch resistance and wear resistance.

[0177] Preferably, according to the present invention, a method for preparing the chemically strengthened glass is also provided, which comprises: performing ion exchange on the substrate glass.

[0178] The present invention has no limitation on the method for preparing the substrate glass, and those skilled in the art can prepare the substrate glass according to the prior art, which will not be described in detail here.

[0179] The ion exchange process includes: firstly performing a primary ion exchange in a sodium-containing molten salt, and then performing a secondary ion exchange in a potassium-containing molten salt.

[0180] The sodium-containing molten salt contains 10wt%-100wt% of sodium salt, and the potassium-containing molten salt contains 95%-100wt% of potassium salt.

[0181] It should be understood that the sodium-containing molten salt and the potassium-containing molten salt of the present invention are both composed of sodium salt and potassium salt. Preferably, the sodium salt is selected from at least one of sodium nitrate, sodium sulfate and sodium carbonate, preferably sodium nitrate. Preferably, the potassium salt is selected from at least one of potassium nitrate, potassium sulfate and potassium carbonate, preferably potassium nitrate.

[0182] Preferably, the conditions for the primary ion exchange include: a temperature of 400-480° C., preferably 430-450° C., and a time of 1-10 h, preferably 4-6 h.

[0183] Preferably, the conditions for the secondary ion exchange include: a temperature of 400-480° C., preferably 430-450° C., and a time of 0.5-5 h, preferably 1-3 h.

[0184] In a third aspect, the present invention provides a glass device, wherein the glass device is made of the chemically strengthened glass described in the first aspect or the substrate glass described in the second aspect.

[0185] In a fourth aspect, the present invention provides an electronic device comprising a cover, wherein the cover comprises the chemically strengthened glass described in the first aspect.

[0186] The electronic device described in the present invention includes but is not limited to at least one of a mobile phone, a display, a tablet computer, an electronic watch, a smart wearable (such as a smart bracelet, a smart watch, smart glasses, etc.), a car-mounted device, an aircraft-mounted device, and a television.

[0187] The present invention is described in detail below with reference to specific embodiments.

[0188] Example 1

[0189] The preparation method of chemically strengthened glass is as follows:

[0190] The substrate glass was prepared according to the substrate glass raw material ratio in Table 1.

[0191] Specifically, the above raw materials are taken according to the formula, with a total mass of 1600 g, 0.4 wt % of a clarifier sodium chloride (6.4 g NaCl) is added, and the mixture is fully mixed to obtain a mixture.

[0192] The mixture was placed in a platinum crucible, heated to 1650℃ in a high-temperature melting furnace to melt for 10 hours, then poured into a molding mold to cool and shape, cooled to 800℃, placed in an annealing furnace, and annealed at 560℃ for 2000min; then cooled to 500℃ for 300min, kept warm for 300min, cooled to 400℃ for 300min, kept warm for 300min, cooled to 300℃ for 300min, and kept warm for 300min, to achieve gradient slow cooling; then cooled to room temperature with the furnace to obtain glass bricks; the obtained glass bricks were shaped and cut using a multi-wire cutting machine to obtain glass sheets with a length, width and thickness of 50mm×50mm×0.7mm (specification size) and a thickness of 0.7mm; then precision machining (CNC), thinning, and polishing were performed to obtain the substrate glass sample to be chemically strengthened. The thickness of the substrate glass is very small compared to the thickness of the chemically strengthened glass obtained by chemically strengthening the substrate glass, and can be ignored.

[0193] Test the Vickers hardness, Young's modulus, fracture toughness, CT_LD of the substrate glass sample max , bifurcation threshold, and the results are shown in Table 1.

[0194] The substrate glass sample is subjected to the first step strengthening in a pure sodium salt bath, and the glass after the first step strengthening is subjected to the second step strengthening in a pure potassium salt bath, thereby obtaining chemically strengthened glass. The conditions (temperature and time) of the first step strengthening and the conditions (temperature and time) of the second step strengthening are respectively shown in Table 1. The Vickers hardness, surface CS, DOL_1, DOL_0, CT_LD of the glass after strengthening, and the calculated value of (surface CS / 1000)×0.7+(CT_LD / 40000)×0.3 are tested, and the results are shown in Table 1.

[0195] Comparative Example 1-Comparative Example 7

[0196] The method is carried out in accordance with Example 1, except that the composition and strengthening process parameters in Table 1 are used, and the other parameters are the same as those in Example 1. Corresponding performance tests are carried out, and the result data are shown in Table 1, Table 3, and Table 4.

[0197] Example 2-Example 7

[0198] The method is carried out in accordance with Example 1, except that the composition and strengthening process parameters in Table 2 are used, and the other parameters are the same as those in Example 1. Corresponding performance tests are carried out, and the results are shown in Tables 2, 3 and 4.

[0199] Test Case

[0200] Taking the chemically strengthened glass obtained in Examples 1-3 and Comparative Examples 1-7 as examples, the scratch area and optical haze were tested under different weight conditions (the testing method is as described in the above specific implementation method), and the result data are shown in Table 3. The scratch pictures of Comparative Examples 1-7 are shown in Table 3. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 As shown; the scratch pictures of Example 1, Example 2, and Example 3 are respectively as shown Figure 8 , Fig. 9 , Fig.10 shown.

[0201] The ratio of the scratch area increment to the haze increment corresponding to the adjacent weights is calculated, and the results are shown in Table 4. The ratio of the scratch area increment to the haze increment shows an overall downward trend. Among them, the calculation formula for the scratch area increment under the weight interval corresponding to the corresponding increment is: the scratch area under the adjacent heavier weight (such as 50g) - the scratch area under the lighter weight (such as 0g); similarly, the calculation formula for the haze increment is: the haze under the adjacent heavier weight (such as 50g) - the haze under the lighter weight (such as 0g); thus, the ratio is calculated.

[0202] Table 1

[0203]

[0204]

[0205] in,

[0206] G=SiO2×7.5+Al2O3×24+B2O3×2-P2O5×6+MgO×31.5+SrO×20+Y2O3×66+La2O3×57+Na2O×10.8+Li2O×25+K2O×7+ZnO×6.1+ZrO2×27;

[0207] M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

[0208] Table 2

[0209]

[0210]

[0211] Table 3

[0212]

[0213] Table 4

[0214]

[0215] It can be seen from Tables 1-2 and 3 that the embodiment of the present invention that satisfies: surface CS ≥ 900 MPa, (surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00, and Young's modulus>85 GPa, has a scratch area of ​​less than 0.6 mm under a load of 50 g. 2 ; Under a load of 200g, the scratch area is less than 1.5mm 2 ; and the haze is also significantly lower; which means that the chemically strengthened glass of the present invention has excellent scratch resistance, and its optical properties change little and can meet the use requirements. However, for the comparative examples that do not meet the above three conditions, the scratch area under the corresponding conditions is significantly larger than that of the present invention, the haze is significantly larger, and the optical properties are greatly affected.

[0216] Moreover, the solution that satisfies the specific composition of the present invention and the component contents satisfy a certain relationship (such as the formula of M and G) can enable the chemically strengthened glass to have the above-mentioned three stress structure characteristics, thereby having excellent scratch resistance.

[0217] From Table 3 and Figure 1-Figure 10It can be seen that compared with the comparative solution, the edge chipping of the embodiment of the present invention is significantly reduced, and under a weight load of no more than 200g, the scratch does not produce edge chipping or the area of ​​the scratch produced edge chipping does not exceed 5% of the total scratch area. In addition, when the glass has obvious edge chipping, the haze value of the glass increases significantly.

[0218] It can be seen from Table 4 that the ratio of the scratch area increment to the haze increment shows an overall downward trend. Combined with the inventor's research, as the weight load increases, the possibility of edge collapse increases, resulting in an increase in the scratch area and an increase in haze. The impact of edge collapse on haze is greater than that on the scratch area, so the ratio of the scratch area increment to the haze increment shows a decreasing trend.

[0219] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A The scratch-resistant chemically strengthened glass comprises a compressive stress layer and a tensile stress layer, wherein: The chemically strengthened glass satisfies: Surface CS ≥ 900MPa; (Surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.00, where CT_LD is the tensile stress linear density, in MPa / mm; Young's modulus>85GPa.

2. The chemically strengthened glass according to claim 1, wherein: When a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester, and a scratch with a length of 4.6 mm is formed on the surface of the chemically strengthened glass under a load of 50 g, the area of ​​the scratch is less than 0.6 mm 2 .

3. The chemically strengthened glass according to claim 1, wherein: When a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° by an automatic pencil hardness tester, and a scratch with a length of 4.6 mm is formed under a load of 200 g, the area of ​​the scratch is less than 1.5 mm 2 .

4. The chemically strengthened glass according to claim 1, wherein: When a Mohs hardness pen with a hardness level of 8 is fixed at an angle of 45° using an automatic pencil hardness tester, and a load of no more than 200 g is used to scratch the surface of the chemically strengthened glass to form a scratch with a length of 4.6 mm, the scratch does not produce edge chipping or the area of ​​the scratch with edge chipping does not exceed 5% of the total area of ​​the scratch.

5. The chemically strengthened glass according to claim 1, wherein: The surface CS of the chemically strengthened glass is ≥1000 MPa.

6. The chemically strengthened glass according to claim 1, wherein: The surface CS of the chemically strengthened glass is 1000 MPa-1600 MPa.

7. The chemically strengthened glass according to claim 6, wherein: The surface CS of the chemically strengthened glass is 1100 MPa-1600 MPa.

8. The chemically strengthened glass according to claim 1, wherein: The chemically strengthened glass satisfies: 2.00≥(surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.

00.

9. The chemically strengthened glass according to claim 8, wherein: The chemically strengthened glass satisfies: 1.50≥(surface CS / 1000)×0.7+(CT_LD / 40000)×0.3>1.

10.

10. The chemically strengthened glass according to claim 1, wherein: The CT_LD of the chemically strengthened glass is ≥40000 MPa / mm.

11. The chemically strengthened glass according to claim 10, wherein: The CT_LD of the chemically strengthened glass is 40000 MPa / mm-66000 MPa / mm.

12. The chemically strengthened glass according to claim 11, wherein: The CT_LD of the chemically strengthened glass is 44000MPa / mm-66000MPa / mm.

13. The chemically strengthened glass according to claim 1, wherein: The Young's modulus of the chemically strengthened glass is ≥90 GPa.

14. The chemically strengthened glass according to claim 13, wherein: The Young's modulus of the chemically strengthened glass is 90 GPa-110 GPa.

15. The chemically strengthened glass according to claim 14, wherein: The Young's modulus of the chemically strengthened glass is 91 GPa-110 GPa.

16. The chemically strengthened glass according to claim 1, wherein: The chemically strengthened glass further satisfies: 0<DOL_1≤0.014t, wherein t is the thickness of the chemically strengthened glass, and DOL_1 is the depth of a compressive stress layer formed on any surface of the chemically strengthened glass by sodium-potassium exchange.

17. The chemically strengthened glass according to claim 16, wherein: The chemically strengthened glass also satisfies: 0<DOL_1≤0.010t, wherein t is the thickness of the chemically strengthened glass, and DOL_1 is the depth of a compressive stress layer formed on any surface of the chemically strengthened glass by sodium-potassium exchange.

18. The chemically strengthened glass according to claim 1, wherein: The chemically strengthened glass further satisfies: 0.14t≤DOL_0≤0.25t, wherein t is the thickness of the chemically strengthened glass, and DOL_0 is the depth of the compressive stress layer, in μm.

19. The chemically strengthened glass according to claim 18, wherein: The chemically strengthened glass also satisfies: 0.14t≤DOL_0≤0.19t, wherein t is the thickness of the chemically strengthened glass, and DOL_0 is the depth of the compressive stress layer, in μm.

20. The chemically strengthened glass according to claim 1, wherein: The Vickers hardness of the chemically strengthened glass is ≥650kgf / mm 2 .

21. The chemically strengthened glass according to claim 20, wherein: The Vickers hardness of the chemically strengthened glass is 670 kgf / mm 2 -750kgf / mm 2 .

22. The chemically strengthened glass according to claim 1, wherein The bifurcation threshold of the chemically strengthened glass is 40000MPa / mm-60000MPa / mm, and CT_LD≤1.10×the bifurcation threshold.

23. The chemically strengthened glass according to claim 1, wherein: Measured in molar percentage of oxides, the composition of the chemically strengthened glass tensile stress layer includes: a SiO2 content of 50.0%-80.0%, an Al2O3 content of 3.0%-20.0%, a Y2O3 content of 0.5%-10.0%, a La2O3 content of 0-10.0%, a MgO content of 0-15.0%, a Na2O content of 1.0%-10.0%, and a Li2O content of 1.0%-20.0%.

24. The chemically strengthened glass according to claim 1, wherein Measured in molar percentage of oxides, the composition of the chemically strengthened glass tensile stress layer includes: a SiO2 content of 60.0%-70.0%, an Al2O3 content of 8.0%-15.0%, a Y2O3 content of 1.5%-6.0%, a La2O3 content of 0%-2.0%, a MgO content of 1.0%-7.5%, a Na2O content of 3.0%-6.0%, and a Li2O content of 8.0%-12.0%.

25. The chemically strengthened glass according to claim 24, wherein: In terms of molar percentage of oxides, the chemically strengthened glass tensile stress layer also comprises: a ZrO2 content of 0-10%, a P2O5 content of 0-8%, and a SrO content of 0-10%.

26. The chemically strengthened glass according to any one of claims 23 to 25, characterized in that: The composition of the chemically strengthened glass tensile stress layer satisfies: The content is expressed as a molar percentage of the oxide, and the value of G is calculated based on the following formula: G≥1250, G=SiO2×7.5+Al2O3×24+B2O3×2-P2O5×6+MgO×31.5+SrO×20+Y2O3×66+La2O3×57+Na2O×10.8+Li2O×25+K2O×7+ZnO×6.1+ZrO2×27.

27. The chemically strengthened glass according to any one of claims 23 to 25, characterized in that: Measured in terms of the content expressed as a molar percentage of oxides, the composition of the chemically strengthened glass tensile stress layer satisfies: Na2O×(3Y2O3+Al2O3)>80.

28. The chemically strengthened glass according to claim 26, wherein: Measured in terms of the content expressed as a molar percentage of oxides, the composition of the chemically strengthened glass tensile stress layer satisfies: Na2O×(3Y2O3+Al2O3)>80.

29. The chemically strengthened glass according to any one of claims 23 to 25, characterized in that: In terms of content expressed as a molar percentage of oxides, the composition of the chemically strengthened glass tensile stress layer satisfies: Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1.

30. The chemically strengthened glass according to claim 26, wherein: In terms of content expressed as a molar percentage of oxides, the composition of the chemically strengthened glass tensile stress layer satisfies: Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1.

31. The chemically strengthened glass according to any one of claims 23 to 25, characterized in that: The composition of the chemically strengthened glass tensile stress layer satisfies: The content is expressed as a molar percentage of the oxide, and the value of M is calculated based on the following formula, M≥12, M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

32. The chemically strengthened glass according to claim 26, wherein: The composition of the chemically strengthened glass tensile stress layer satisfies: The content is expressed as a molar percentage of the oxide, and the value of M is calculated based on the following formula, M≥12, M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

33. The chemically strengthened glass according to claim 29, wherein: The composition of the chemically strengthened glass tensile stress layer satisfies: The content is expressed as a molar percentage of the oxide, and the value of M is calculated based on the following formula, M≥12, M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

34. The chemically strengthened glass according to claim 26, wherein: The composition of the chemically strengthened glass tensile stress layer satisfies: the value of G calculated by the content expressed as the molar percentage of the oxide is G≥1350.

35. The chemically strengthened glass according to claim 29, wherein: The composition of the chemically strengthened glass tensile stress layer satisfies the following condition: 1<Li2O / (Na2O+K2O)≤4.0, in terms of the content expressed as molar percentage of oxides.

36. The chemically strengthened glass according to claim 31, wherein: The composition of the chemically strengthened glass tensile stress layer satisfies: the value of M calculated by the content expressed as the molar percentage of the oxide is 12≤M≤35.

37. A method for preparing a composition comprising The substrate glass of the scratch-resistant chemically strengthened glass is characterized in that The composition of the substrate glass includes, in terms of molar percentage of oxides: 50.0%-80.0% SiO2, 3.0%-20.0% Al2O3, 0.5%-10.0% Y2O3, 0-10.0% La2O3, 0-15.0% MgO, 1.0%-10.0% Na2O, and 1.0%-20.0% Li2O; The composition of the substrate glass satisfies the following conditions, expressed in terms of the content expressed as a molar percentage of oxides: The value of G is calculated based on the following formula, G ≥ 1250, G = SiO2 × 7.5 + Al2O3 × 24 + B2O3 × 2-P2O5 × 6 + MgO × 31.5 + SrO × 20 + Y2O3 × 66 + La2O3 × 57 + Na2O × 10.8 + Li2O × 25 + K2O × 7 + ZnO × 6.1 + ZrO2 × 27; Na2O×(3Y2O3+Al2O3)>80.

38. The substrate glass according to claim 37, characterized in that: Measured in molar percentage of oxides, the composition of the substrate glass includes: SiO2 content of 60.0%-70.0%, Al2O3 content of 8.0%-15.0%, Y2O3 content of 1.5%-6.0%, La2O3 content of 0%-2.0%, MgO content of 1.0%-7.5%, Na2O content of 3.0%-6.0%, and Li2O content of 8.0%-12.0%.

39. The substrate glass according to claim 37, characterized in that: The composition of the substrate glass further satisfies the following conditions, measured in terms of the content expressed as a molar percentage of oxides: Li2O+Na2O+K2O≤17.0, and Li2O / (Na2O+K2O)>1; and / or The value of M is calculated based on the following formula, M≥12, M=Li2O×(1.4×Y2O3+1.1×La2O3+Al2O3) / (MgO×0.3+Li2O×0.3+K2O+Na2O).

40. The substrate glass according to claim 37, characterized in that In terms of molar percentage of oxides, the composition of the substrate glass also includes: a ZrO2 content of 0-10%, a P2O5 content of 0-8%, and a SrO content of 0-10%.

41. The substrate glass according to claim 37, characterized in that: The Young's modulus of the substrate glass is greater than 85 GPa.

42. The substrate glass according to claim 41, characterized in that The Young's modulus of the substrate glass is 90 GPa-110 GPa.

43. The substrate glass according to claim 42, characterized in that The Young's modulus of the substrate glass is 91 GPa-110 GPa.

44. The substrate glass according to claim 37 or 41, characterized in that: The Vickers hardness of the substrate glass is ≥620kgf / mm 2 .

45. The substrate glass according to claim 44, characterized in that The Vickers hardness of the substrate glass is 630 kgf / mm 2 -750kgf / mm 2 .

46. ​​The substrate glass according to claim 37, characterized in that The bifurcation threshold of the substrate glass is 40000MPa / mm-60000MPa / mm.

47. The substrate glass according to claim 37, characterized in that The composition of the substrate glass satisfies the following conditions based on the content expressed in molar percentage of oxides: the value of G is calculated, G≥1350.

48. The substrate glass according to claim 39, characterized in that The composition of the substrate glass also satisfies the following conditions, measured in terms of the content expressed as a molar percentage of oxides: 1<Li2O / (Na2O+K2O)≤4.0; and / or, the value of M is calculated, 12≤M≤35.

49. A glass device, characterized in that: The glass device comprises the glass component described in any one of claims 1 to 36 It is made from the scratch-resistant chemically strengthened glass or the substrate glass according to any one of claims 37 to 48.

50. An electronic device comprising a cover, characterized in that: The covering member comprises a cover member as claimed in any one of claims 1 to 36 Scratch resistant chemically strengthened glass.

51. The electronic device according to claim 50, characterized in that The electronic device includes at least one of a mobile phone, a display, a tablet computer, an electronic watch, a smart wearable device, a car-mounted device, an aircraft-mounted device, and a television.

Citation Information

Patent Citations

  • Rare earth doped tempered glass ceramic and preparation method and application thereof

    CN111087175A